2001
DOI: 10.1021/ie010225y
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Dynamic Efficiency and Scale-up of a Retreated Blade Impeller CSTR

Abstract: Numerical simulations are used to characterize the fluid dynamic behavior of an industrialsize reactor. First, we focused on an experimental replica (∼440:1 volume ratio) of the full-scale reactor and evaluated the reliability of fully three-dimensional, time-dependent numerical computations of the flow field. An experiment was planned to obtain power data, which were compared with computer simulations for the scaled model, giving good agreement. Next, we examined the full-scale industrial reactor by exploitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 27 publications
3
31
1
Order By: Relevance
“…Thus, the efficiency of this stirrer is quite low. In fact, its power consumption is equivalent to that of an impeller with three curved blades (A=32, Campolo et al, 2002), and is much lower than that of a high-efficiency impeller. For instance, the helical ribbon impeller has a value of 160 (Tanguy et al, 1997).…”
Section: Mixing Efficiencymentioning
confidence: 99%
“…Thus, the efficiency of this stirrer is quite low. In fact, its power consumption is equivalent to that of an impeller with three curved blades (A=32, Campolo et al, 2002), and is much lower than that of a high-efficiency impeller. For instance, the helical ribbon impeller has a value of 160 (Tanguy et al, 1997).…”
Section: Mixing Efficiencymentioning
confidence: 99%
“…Dynamic similarity prevails between two geometrically similar units if all corresponding forces at counterpart locations have a constant ratio (Coulson et al, 1999). Numerical simulations have been used in the scale-up of CSTRs typically used for crystallization, and these correlated well with empirical measurements (Campolo et al, 2002).…”
Section: Discussionmentioning
confidence: 78%
“…A more desirable process would be a continuously stirred tank reactor (CSTR) because installation costs are likely to be comparatively low (Gaterell et al, 2000), it would require limited additional operator training because of the use of CSTRs within the water industry (Kim and Speece, 2002;Lui, 1998), and its simple design reduces the risk of operational failures. The merits of CSTR use also include an understanding of scale-up (Campolo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a few studies regarding the scale up of continuous reactors have been reported. For instance, Campolo et al (2002) used Nagata's correlation (Nagata, 1975 for the scale up of a CSTR from a lab scale to an industrial scale and verified the scale up of the two reactors by comparing the power number, discharge flow number, and pumping efficiency. In another study, the reaction time, heat removal capacity, and the degree of homogeneity were kept constant for the solution and bulk polymerization.…”
Section: Scale Upmentioning
confidence: 99%